Conceiving writing: theoretical and methodological approaches on written production through time - Casasa Núñez, Laura (2023)
This article presents a tour of the various theoretical approaches with which it has been addressed and has tried to explain and teach the process of written production in the educational field. From the bibliographical review, the different classifications that have been made on this subject are firstly proposed. Subsequently, a description is offered about the known theoretical approaches to writing, organized into three categories: textual approaches, cognitive approaches and contextual approaches. Finally, a review is made of some other theoretical-methodological approaches that are currently being incorporated into the exercise of teaching writing. With this document we intend to contribute to the decisions that mediate the teaching of writing in our region, in order to strengthen educational processes for the achievement of more critical, more reflective societies with higher development rates.